An Improved Algorithm for TD-LTE Downlink Time Synchronization - Wenle Bai; Xu Wang; Yongmei Zhang; Mugen Peng (Dianxin kexue)
Aimed at the application problem of timing synchronization algorithm in orthogonal frequency division multiplexing system, an improved algorithm for TD-LTE downlink time synchronization was proposed. It utilizes statistical energy difference and correlation of cyclic prefix to improve the system performance, which reduces the computational complexity, and can detect the cyclic prefix types. The simulation results demonstrate that the performance of the new method is excellent in multi-path fading channels, especially in the case of small SNR. And it is robust against the normalized frequency offset and Doppler shift.